Te kapa o Te Reureu: keeping the home fires burning - Suzanne Vallance; Taruke Karatea; Sarah Edwards (Kōtuitui)
Te Matatini has ensured kapa haka is now a well-recognised form of national entertainment, but this has led to some debate about tradition and contemporaneity, and performance versus deeper politico-cultural kaupapa. Through a case study based in Te Reureu Valley (Manawatū, Aotearoa/New Zealand), we explore the political potential of kapa haka, and highlight the role of ahi kā in this vital kaupapa. When tended by ahi kā, kapa haka (re)forged those crucial relationships between awa, whenua and whānau, and strengthened collective efficacy and political literacy. We conclude that ahi kā play a key role in tending practices like kapa haka so as to help Māori negotiate challenges associated with land loss, fractured land ownership and the underutilisation of land, and navigate complex political contexts.Glossary of Māori words: ahi kā: he fires of occupation; ahi matao: cold fire; ahi tere: flickering flame; awa: river; haka: a ceremonial war dance and part 5 of Te Matatini's format; hapū: kinship group; iwi: extended kinship group; kaihaka: tutor; kākahu: to dress (for kapa haka); kauheke: elder; kaumātua: elder; kaupapa: topic, purpose; kawa: customs of the marae: kete: basket; kōrero: tell, speak, discussion; kōrero tuku iho: knowledge passed down; korowai: cloak, safe space for discussion; mahi tahi: working together; mahi toi: artistic expression; mana motuhake: self-determination, control over one's destiny; marae: complex of buildings; mārakai: gardening for food; mōteatea: a traditional chant and part 2 of Te Matatini's format; ngākau: heart and soul; Pākehā: non-Māori; pakeke: adult; poi: light ball swung on the end of a rope. A poi performance comprises part 3 of Te Matatini's format; pūkenga: skill; pūrākau: legend, story; rangatahi: youth; rūnanga: tribal council, governance board of hapū; taiao: the holistic environment, nature; takiwā: tribal district; tautoko: support; te Ao Māori: Māori world view; te reo: the language, Māori language; Te Tiriti: The Treaty (noting differences in wording between the different versions); tikanga: lore, correct protocol; titiro: look; tupuna: ancestors; uukaipō: homelands; urupā: cemetery; wahine: woman; wāhine: women; wahine toa: female leader; waiata-ā-ringa: an action song. Part 4 of Te Matatini's format; waioratanga: wellbeing; whakaeke: a choreographed entry and part 1 of Te Matatini's format; whakarongo: listen; whakawātea: a choreographed kapa haka exit and the final part of Te Matatini's format; whānau: family group; whanaungatanga: relationships, kinship; whenua: land.